Mediatization and the extimacy process of patients with Turner Syndrome on digital platforms - Pasquali Falchi, Maria do Carmo (Revista Española de Comunicación en Salud, 2023)
Introduction: The digital platforms have become a place for sharing intimate issues, for instance, to talk about one’s own illness, what characterize an extimacy movement, boosted by the mediatization process. This dynamic is commonly used by patients with rare diseases – as Turner Syndrome – due to its low frequency, the stigmas and the unfamiliarity of doctors and people in general. Objectives: Comprehend and analyze how, in the ambience of mediatization, occurs the process of extimacy in patients with Turner Syndrome on the Instagram profile Turner & Eu and on the Butterfly TV YouTube channel. Methodology: Using the Analysis of Discursive Circulation, the meanings contained in two posts of the Instagram profile and in one video of the YouTube channel were studied through an intertextual analysis of the discursive operations. Results: The extimacy process aims no just to expose intimate issues, but it is also a way of self-affirmation, validation, self-organization, inspiration and it enables the end of stigmas, providing a reconfiguration of the illness. Conclusion: The extimacy involves two dimensions: the temporality of each patient and the digital platform where this movement happens. Besides that, it is also a process collaboratively built.
Keywords: mediatization; extimacy; Turner Syndrome; health communication